Purifikasi Islam dalam Gerakan Padri di Minangkabau - Nashir, Haedar (Unisia, 2012)
The Padri Movement, also known as the White Group Movement, grown up in Minangkabau in 1821 – 1837, on one side, had been a strong and militant struggle against Dutch colonization in Sumatra. On the other side, this movement also raised as a power of reform, bringing together a strong and militant mission of Islamic Purification. This movement had raised a violence controversy, both when it conflicted with traditional power and when it expanded its areas of movement to the Batak Land. In the perspective of Sociology, both the Padri Movement and its militant and violence actions brought in every expanded social or religious movement cannot be separated one and each other. This is caused by the fact that such a movement is closely related to a strict religious ideology and faith, and at once it also closely related to a complicated sociological condition at that time. Therefore, a multi-perspective is necessary to understand complicated socio-religious movements. Keywords: Padri Movement, Religious Movement, Islamic Purification.